(untitled) (De Musica, 2021)
The digital revolution is breaking with a millennial musical culture based on reading and writing notes. So far, art music has been composed in the medium of musical scores, and today, not only in popular music but also in art music, samples are becoming the new medium of composition. This is the theory that I would like to defend in the following with a double strategy. On the one hand, I will introduce five pieces of New Music, which were created between 2014 and 2018 and were composed with instrumental samples. On the other hand, I will develop a historical-philosophical argument that explains why such sample compositions actually have a prominent musical-historical significance.